ELECTROMAGNETIC EFFECTS DURING RELAXATION PROCESSES IN THE EARTH'S INHOMOGENEOUS CRUST - Soloviev S.P.; Spivak A.A. (My University, 2007)
This paper reports data on the joint recording of microseismic oscillations and the electric field in nearsurface sectors of the Earth’s crust. Based on the results of their analysis, we propose a model for the source of low-frequency electromagnetic signals as an electric dipole generated by the constrained rotation of structural blocks during the relaxation of a medium with a low moisture content. According to this model, separation of electric charges and generation of currents are related to the breakdown of mechanical bonds between the neighboring blocks during differential motions or to the electric polarization of rock during a dramatic variation in the stressed state. The results show that the value of the electric dipole moment appearing in the active (relaxing) block segment with a linear dimension of ~10 m is as much as 10–7–10–6 C * m during the formation of a system of subparallel fractures in the interblock space and as much as 10–9–10–7 during the electric polarization of rock. In both scenarios, the dipole moment can provide an amplitude of electric pulses equal to 0.01–1 mV/m in the surface layer of the Earth’s crust over distances exceeding the block dimension by two to three orders of magnitude. The parameters of electric pulses obtained in the model and recorded under natural conditions are in good agreement.